The Effect of Community Engagement on Healthcare Utilization and Health Insurance Enrolment in Ghana: Results from a Randomized Experiment - Stephen K. O. Duku; Edward Nketiah-Amponsahd; Christine J. Fenenga; Daniel K. Arhinful; Wendy Janssens; Menno Pradhan (Tinbergen Institute, 2018)
Background: Health insurance enrolment in many Sub-Saharan African countries is low, even with highly subsidized premiums and exemptions for vulnerable populations. This paper evaluates the impact of a community engagement intervention implemented in Ghana with the aim of improving clients' perceptions on service quality and subsequently improving healthcare utilization and health insurance enrolment. Method: We used a panel data of 6,937 individuals from a cluster randomized controlled trial conducted in 64 communities in two regions in Ghana. A random half of communities received the intervention after a baseline survey in April 2012; the remaining communities served as controls. A follow-up survey was conducted in March 2014 to evaluate the intervention. Ordinary Least Squares regression estimations were used to measure the intervention's impact on quality perceptions, and on healthcare utilization and health insurance enrolment for the full and balanced samples of all household members as well as the uninsured at baseline. Results: In the short term (12 months) the intervention did not produce any significant impact on perceptions of service quality, healthcare utilization or health insurance enrolment in the targeted population. It however reduced the frequency of illness by 13.8 percentage points, suggesting an overall improvement in health status. It also resulted in a 7.2 percentage points increase in insurance enrolment for the uninsured. Conclusion: Community engagement has the potential to motivate service providers to improve quality of care. However, this may not lead to improved perception of service quality, and increased healthcare utilization in the short term. Still, engaging clients in community discussions on quality improvements can effectively enhance health insurance uptake among those who were previously uninsured. Further long-term intervention is necessary to investigate its long-term effects.
Keywords: O15; 330; health insurance; Ghana; randomized experiment; community participation